On Chesil Beach [videorecording (DVD)] - Ronan, Saoirse, 1994-; Howle, Billy, 1989-; Duff, Anne-Marie; McEwan, Ian (Universal Pictures Home Entertainment, 2018)
In 1962 England, a young couple find their idyllic romance colliding with issues of sexual freedom and societal pressure, leading to an awkward and fateful wedding night.